Ultrasonic vibration-assisted pelleting for cellulosic biofuels manufacturing: A study on in-pellet temperatures. (April 2015) - Tang, Yongjun; Cong, Weilong; Xu, Jun; Zhang, Pengfei; Liu, Defu
Abstract: Cellulosic biofuels have been proposed to replace part of traditional liquid transportation fuels. Cellulosic biomass is the feedstock in cellulosic biofuel manufacturing. Costs associated with collection and transportation of cellulosic biomass account for more than 80 percent of the feedstock cost[1] . By processing cellulosic biomass into pellets, energy density and handling efficiency of cellulosic feedstock can be improved, resulting in reduction of transportation and handling costs. Ultrasonic vibration-assisted (UV-A) pelleting is one of important pelleting process which can make high quality pellets efficiently. The literature on UV-A pelleting covers studies about effects of input process parameters on pellet density, durability, sugar yield, charring, and pelleting force, but has little information about pelleting temperature. This paper presents an experimental investigation on effects of input variables on pelleting temperature. The pelleting temperatures at the different locations of a pellet were measured during pelleting using metal wire-typed thermocouples. Several pelleting parameters were varied to study their effects on pelleting temperature. Results obtained will be helpful in understanding why pelleting parameters affect pellet quality (density and durability), charring, and sugar yield. Highlights: An experimental investigation on in-pellet temperatures in ultrasonic vibration-assisted pelleting has been conducted. The temperatures are measured in different locations of biomass pellet. The relationship between input variables and temperatures can be built. Obtained results can provide valuable explanations on pellet charring, quality, and sugar yield.